Heartstopper. Volume 4 - Oseman, Alice (Oseman, Alice. Heartstopper ;, 2021)
Charlie and Nick are both thinking about saying the three little words that can make or break a relationship: I love you. Nick wants to come out to his dad, but he is struggling with finding the right words. Charlie's feelings about food continues to worsen, but he doesn't know how to tell his parents. With school starting up again, Charlie's mental health takes a turn, and he takes the first steps towards getting professional help.